NATURAL AND ANTHROPIC RISK STUDIES IN FOUR DECADES IN THE GEOGRAPHICAL JOURNAL OF CENTRAL AMERICA (1974 - 2015) - Quesada-Román, Adolfo (2017)
The aim of this work is to identify the influence of the international and national epistemological trends and the techniques in the risk management of disasters (RMD) in Costa Rica. To do this, the journal papers of the Geographical Journal of Central America between 1974 and 2015 were analyzed -114 included topics related to natural and anthropogenic risks. They were classified into eight thematic classes: seismic hazards, volcanic hazards, slope processes hazards, hydrometeorological hazards, climate change, environmental degradation and soil erosion, vulnerability, and epistemology of risk management disasters in Costa Rica and Latin America. As a result of this work, it was possible to identify a significant increase in jobs related to the GRD from the late 1980’s, with a clear diversification of the issues addressed.